Hemerophytes of the State Dendrological Park “Trostianets” of the NAS of Ukraine (Chernihiv oblast, Ukraine): history of plantation formation, current state of acclimatization and naturalization, and distribution of invasive plants - Oleksandr Shynder; Maryna Tarabun; Vitaliy Kolomiychuk (Інтродукція Рослин)
This study analyzes the acclimatization and naturalization processes of hemerophytes in the State Dendrological Park “Trostianets” of the National Academy of Sciences of Ukraine (Chernihiv Oblast, Ukraine). The research focuses on the systematic and ecological assessment of 151 alien plant species that were introduced to the park for cultivation. The study reveals that 72 species have escaped from the cultivation area and are actively naturalizing within the park’s spontaneous flora, while 79 species remain within managed plantations. Due to active naturalization, in the spontaneous flora on the park’s territory, among 123 wild alien plants, the majority (58.5 %) are ergasiophygophytes. Among ergasiophygophytes, woody plants predominate (73.6 %). The systematic composition of naturalized species indicates dominance of eudicots (125 species), followed by gymnosperms (18 species) and monocots (seven species). Woody plants, including trees, shrubs, and lianas (the total share is 82.1 %) demonstrate the highest potential for long-term acclimatization and further expansion beyond cultivated areas. By geographical origin, the largest number of acclimatized hemerophytes originates from North America (34.4 %), Asia (24.5 %), and the regions of the Ancient Mediterranean (20.6 %). The research highlights 16 invasive species, with 12 already forming spontaneous populations in the park. Among them, Acer negundo, Parthenocissus inserta, Robinia pseudoacacia, Quercus rubra, and Fraxinus pennsylvanica are actively spreading, forming dense populations within and beyond the park boundaries. Potentially invasive taxa, such as Ailanthus altissima, also demonstrate the ability to establish self-sustaining populations. The spread of certain species, particularly woody lianas like Clematis vitalba and Vitis riparia, suggests a high potential for ecological transformation of local habitats.